Guru Sebagai Teladan: Analisis QS Al-Ahzab Ayat 21 - Darwin, Darwin; Nasution, Fahruddin (LaKaspia, 2023)
- The presence of a teacher in the educational process is a very important and irreplaceable aspect. Even though technology has developed rapidly, the presence of a teacher is still absolutely necessary. However, there is still a phenomenon in which the world of education continues to show that there are still teachers who carry out their work irresponsibly and are far from being exemplary as they should be. It is still easy to find teachers who teach sparingly, is apathetic, feel burdened, and are forced to teach so that the exemplary and noble values of the teacher become empty. This article aims to discuss about teachers as role models based on an analysis of QS Al-Ahzab verse 21. This article uses a literature study approach. This study shows that the specific context of QS Al-Ahzab verse 21 is speaking in conditions of Khandaq's war, but the meaning of this verse applies in general. The attitude of Rasulullah SAW is an ideal attitude that can be used as an example by a teacher in carrying out his role in the world of education. The teacher must be a role model, manifested in the form of patience, steadfastness, readiness, struggle, and surrender to Allah SWT when carrying out his duties as a teacher. By doing this, the teacher will be able to set an example like the attitude of Rasulullah SAW, which Allah SWT later praised through QS Al Ahzab 21. Abstrak Kehadiran seorang guru dalam proses pendidikan merupakan salah satu aspek yang sangat penting dan tak tergantikan. Meski teknologi telah berkembang pesat namun kehadiran seorang guru tetap mutlak diperlukan. Namun demikian, masih terdapat fenomena di mana dunia pendidikan terus menunjukkan bahwa masih terdapat guru yang melakukan pekerjaannya dengan tidak bertanggung jawab dan masih jauh dari keteladanan sebagaimana mestinya. Masih mudah ditemukan guru yang mengajar sekedarnya saja, bersifat apatis, merasa beban dan terpaksa dalam mengajar, sehingga nilai-nilai keteladanan dan kemuliaan guru menjadi hampa. Artikel ini bertujuan untuk mendiskusikan tentang guru sebagai teladan berdasarkan analisis terhadap QS Al-Ahzab ayat 21. Artikel ini menggunakan pendekatan studi literatur. Kajian ini menunjukkan b bahwa konteks khusus QS Al-Ahzab ayat 21 adalah berbicara dalam kondisi perang, yaitu perang khandaq, namun makna ayat ini berlaku secara umum. Sikap Rasulullah SAW merupakan sikap ideal yang dapat dijadikan contoh oleh seorang guru dalam menjalankan perannya dalam dunia pendidikan. Guru harus mampu menjadi suri teladan yang termanifestasi dalam bentuk kesabaran, teguh hati, siap siaga, penuh perjuangan, dan berserah diri kepada Allah SWT ketika menjalankan tugasnya sebagai seorang guru. Dengan melakukan hal tersebut, maka guru akan dapat menjadi teladan sebagaimana sikap Rasulullah SAW yang kemudian dipuji oleh Allah SWT melalui QS Al Ahzab 21.